2001
DOI: 10.1074/jbc.m009969200
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Linked Heme in Cytochrome P4504A Fatty Acid Hydroxylases

Abstract: Three independent experimental methods, liquid chromatography, denaturing gel electrophoresis with heme staining, and mass spectrometry, establish that the CYP4A class of enzymes has a covalently bound heme group even though the heme is not cross-linked to the protein in other P450 enzymes. Covalent binding has been demonstrated for CYP4A1, -4A2, -4A3, -4A8, and -4A11 heterologously expressed in Escherichia coli. However, the covalent link is also present in CYP4A1 isolated from rat liver and is not an artifac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
93
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(100 citation statements)
references
References 30 publications
6
93
1
Order By: Relevance
“…Therefore, the ω-hydroxylation regiospecificity of CYP4A enzymes is of critical physiological importance. We previously (a) postulated that a constricted access channel controls ω-hydroxylation, (b) discovered that the heme is covalently bound to the protein in most CYP4 enzymes, (c) identified the residue involved in the covalent linkage, and (d) proposed that covalent heme binding is important for the architecture of the narrow channel [17,33,34]. It is thus somewhat unexpected that CYP52A21 from C. albicans predominantly hydroxylates fatty acids at the ω-position (Figure 4) despite the fact that the Glu residue involved in heme-covalent binding in CYP4A enzymes is replaced in CYP52A21 by an Ala and its heme is not covalently bound ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the ω-hydroxylation regiospecificity of CYP4A enzymes is of critical physiological importance. We previously (a) postulated that a constricted access channel controls ω-hydroxylation, (b) discovered that the heme is covalently bound to the protein in most CYP4 enzymes, (c) identified the residue involved in the covalent linkage, and (d) proposed that covalent heme binding is important for the architecture of the narrow channel [17,33,34]. It is thus somewhat unexpected that CYP52A21 from C. albicans predominantly hydroxylates fatty acids at the ω-position (Figure 4) despite the fact that the Glu residue involved in heme-covalent binding in CYP4A enzymes is replaced in CYP52A21 by an Ala and its heme is not covalently bound ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the CYP4 enzymes have evolved a strategy that allows them to specifically direct the reaction to the terminal (ω-) carbon of the fatty acid chain. We have postulated that this strategy involves a constricted access channel through which the fatty acid terminus must be threaded for oxidation, have proposed that covalent binding of the heme to the protein facilitates the assembly of a sufficiently rigid access channel, and have used terminally halogenated fatty acids to obtain information on the effective diameter of the CYP4A channel [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In studies of rat liver CYP4A1, a conserved glutamate residue (Glu 318 in this isoform) was found to be the amino acid residue to which the heme had become esterified. The importance of the covalent linkage of heme to the activity of this P450 enzyme was demonstrated through mutagenesis of key residues, although the activity in other CYP4A isoforms may not be so sensitive to the extent of covalent ligation of the heme to the protein (24,25). Studies on mammalian CYP4A1, CYP4A3, and CYP4A11 confirmed that covalent heme linkage to the protein is autocatalytic and occurs because of esterification with the glutamate via the heme 5-methyl group (25).…”
mentioning
confidence: 88%
“…An alignment of amino acid sequences from various members of the CYP4 family of fatty acid-oxygenating P450 enzymes was performed using the ClustalW sequence alignment program via the European Bioinformatics Institute (available at www.ebi.ac.uk/clustalw/). The sequence alignment shown is for residues in the I helix region of the P450 enzymes, surrounding the conserved glutamate residue shown to participate in covalent linkage of the heme group in eukaryotic CYP4 enzymes (23,24). The relevant amino acids at this position in the alignment are shown in boldface and are underlined.…”
Section: Expression and Purification Of Wild-type And Mutant P450 Bm3mentioning
confidence: 99%
See 1 more Smart Citation